Tribute to a Great Historian and Professor: Juan Carlos Garavaglia. Lessons and Topics for the Historiographic Agenda in Costa Rica - Rodríguez Solano, Pablo Augusto (2019)
This article is a tribute to Juan Carlos Garavaglia, who died on January 15, 2017, in France. It begins by presenting the context of his life, as frame to understand the person, beyond the historian, making a quick review of his life and personality. This allows us to approach his production from his main feature, his humanity, always present in his work, it was a feature that always pushed him to rescue people as actors of history, who at their relational level are those who create and nourish institutions, surpassing with this a superstructural approach to the discipline. Finally, we will review some of his contributions, from which to rescue some of the main lessons of his work for a possible research agenda in Costa Rica.